OSS-BASED NIB REGISTRATION FOR MSME CAKEY BAKEY CO AND JOYI BAKES - Wilda Lim; Windi Afdal (Universitas Internasional Batam, 2022)
Licensing in establishing a business has a legal basis contained in Government Regulation number 24 of 2018 concerning Electronically Integrated Business Licensing Services, where in the regulation it is explained that OSS (Online Single Submission) is a business license issued by the OSS Institution intended and on behalf of the minister. , leaders, institutions, governors, mayors or regents to business actors in carrying out their business. OSS is a product of government that is growing along with advances in technology. With the OSS, business actors who run MSMEs are made easier in the process of registering their businesses to get legal certainty, legal protection, and of course get their right to run a business. The purpose of writing this Community Service is specifically to assist partners in assisting in making OSS-based business legalities. In this Community Service activity, data collection techniques that are more widely used are online interviews and documentation for each stage of registration on the OSS website. Thus, the output of activities that have been achieved in Community Service is obtaining a NIB issued by the OSS institution, which will be used by business actors Cakey Bakey Co and Joyi Bakes to conduct business activities. In this Community Service activity, data collection techniques that are more widely used are online interviews and documentation for each stage of registration on the OSS website. Thus, the output of activities that have been achieved in Community Service is obtaining a NIB issued by the OSS institution, which will be used by business actors Cakey Bakey Co and Joyi Bakes to conduct business activities. In this Community Service activity, data collection techniques that are more widely used are online interviews and documentation for each stage of registration on the OSS website. Thus, the output of activities that have been achieved in Community Service is obtaining a NIB issued by the OSS institution, which will be used by business actors Cakey Bakey Co and Joyi Bakes to conduct business activities.